Particle identification with the ALICE transition radiation detector - Pachmayer, Yvonne C. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2014)
The Transition Radiation Detector (TRD) provides particle identification in the ALICE central barrel. In particular, it allows electron identification via the measurement of transition radiation for p>1GeV/c, where pions can no longer be rejected sufficiently via specific energy loss in the ALICE Time Projection Chamber. The ALICE TRD is uniquely designed to record the time evolution of the signal, which allows even better electron/pion separation. In addition, the electron identification capability of the TRD can be used on-line to trigger at level 1. The particle identification and its performance in pp, p-Pb and Pb-Pb collisions employing various methods, such as truncated mean signal, one- and two-dimensional likelihood on integrated charge and neural network, will be presented. The measurement of J/ψ mesons in Pb-Pb collisions is given as a case study to show how well the TRD contributes to physics analyses due to its excellent pion suppression.
Gesehen am 04.11.2020